The results of the development of nursing practice guidelines in the care of patients with acute ischemic stroke Accident and Emergency Work, Fang Hospital, Chiang Mai Province - ไชยอาม สุรุ่งนภา (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2022)
Stroke is a severe neurological disease that affects patients, treatments are to reduce dangers to the brain tissue as much as possible. The patients who receive service delays are likely to have disability or death. This study was a developmental study. The objective were 1) to study the effect of nursing practice guidelines caring for patients with acute ischemic stroke. in accidents and emergencies, Fang Hospital and 2) to develop the use of nursing practices in caring for ischemic stroke patients’ acute period of blood in accidents and emergencies, Fang Hospital The sample was 12 new patients with symptoms concomitant to acute ischemic and indications for fibrinolytic drugs from September 1, 2021, to February 28, 2022. The research instrument were an opinion questionnaire of accident and emergency nurses and an evaluation form of nursing practice in caring for acute ischemic stroke patients. The data were analyzed by descriptive statistics consisting of frequency, percentage, mean and standard deviation. The results showed that 85.76 percent of accident and emergency nurses were satisfied and able to use the guidelines at a high level. The mean time of treatment with a fibrinolytic drug (rt-PA) <60 minutes was 50.08 minutes accounting for 83.33 percent. The patients who received the drug over 60 minutes had a disability /stable condition rate of 2 cases, or 16.66 percent. The nursing practice guideline in the care of acute ischemic stroke patients as a tool to assist in decision-making among the treating nurses. The stroke-specific symptoms assessed and key data collected completely.